(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
Eye contact is important for the development of several verbal skills. This study evaluated the effect of equivalence class formation (ECF) comprising figures of faces and a preferred item on observation responses to faces in children with ASD. Two boys (4 and 5 years old) participated in the study. Initially, we evaluated the observation responses to faces in tests in structured (play) and natural situations (experimenter entering the room, greeting or not the child). Then, all the training and testing for ECF was carried out, with the baseline discriminations comprising identity matching wit class-specific consequences. Face observation tests were conducted again. The results show an increase in the frequency and duration of attention responses to faces. There was also an increase in the preference for figures of faces. Such data encourage the continuity of research that explores the applied potential of ECF.